Analisis Perbedaan Intensi Berwirausaha Mahasiswa Pertanian Berdasarkan Keikutsertaan Dalam Kuliah Kewirausahaan (Analysis of Differences in Entrepreneurial Intentions of Agricultural Students Based on Participation in Entrepreneurship Courses) - Ningsih, Yesi Mustika; Leilasariyanti, Yennyka; Ramadhani, Mirza (Jurnal Ilmiah Sosio Agribis, 2025)
This study analyzes whether there is a significant difference in entrepreneurial interest in agricultural students based on taking entrepreneurship courses. The data shows that entrepreneurial interest in the agricultural sector is still relatively low, indicated by the small number of students who enter the field. The study used a descriptive quantitative method with the Mann-Whitney U test analysis technique. The sample consisted of 150 active students from three state universities in East Java, namely UPN "Veteran" East Java, Brawijaya University, and Trunojoyo University Madura. There are statistical results that entrepreneurship courses have an effect on students' entrepreneurial intentions, with a p value of 0.036 which is significant at the α level of 0.05. Thus, the null hypothesis stating that there is no difference between the two groups is rejected.Keywords: Intention, Entrepreneurship, Agriculture Students